The effect of geotechnical uncertainty on the preliminary design of large diameter monopiles - ICASP14; Reale, Cormac; Igoe, David (My University, 2023)
The offshore wind industry has evolved over the past decade with significant technological advances. These have been driven by the need for offshore wind energy to provide cost-competitive renewable energy. The economics of offshore wind necessitates lean and efficient designs and nowhere is this more prevalent than in the turbine foundations. This paper examines the impact of geotechnical spatial variability on the design of large diameter monopiles supporting offshore wind turbines (OWTs). Monte Carlo simulations are used to examine the reliability and probability of failure monopile geometries designed using a deterministic methods.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED